Harvesting Electrical Energy from Rooftop Ventilator - Lau, Khai Xin; Leow, Pei Ling; Jamani, Jasrul Jamian; Arsat, Rashidah; Abdeltawab, Amr Ahmed Abdelsattar; Rahman, Syed Salman; Abd Khalid, Nur Hafizah; Mohamed, Azman; Abd Khalid, Ismayuddin (International Journal of Integrated Engineering, 2018)
Development of the renewable energy is one of the most challenging issue in Malaysia since the fossil fuels and natural gas is foresee to be depleted in one day. Renewable energy is able to provide sustainable yet clean energy to the country in the near future. Other than Solar, wind energy is only of the renewable energy that has the potential to provide green energy to not only domestic but industrial users. This paper proposes a development of similar concept of wind energy by harvesting electrical energy from rooftop ventilator. Modification is made on a commercial rooftop ventilator with an integration of a 120V DC motor and conversion gear (gear ratio 1:2) to the turbine shaft. The continuous rotation of the rooftop ventilator due to temperature difference indoor and outdoor rotated the rotor of the DC generator. The DC energy is stored in the battery via a charge controller before distributing to the load. An average of 60 rpm turning speed of the ventilator is simulated mimicking the general turning speed of the ventilator installed on the roof. The generated energy characteristics study is carried out by using standard fan to produce steady rotational of the ventilator. As the spin rate is very low to reach the optimum spin rate, the generated energy is small and only for a small DC load.